Закладка, развитие и рост пястных костей рукокрылых (Chiroptera) - Ковтун, М.Ф.; Леденев, С.Ю.; Сыч, В.Ф. (Вестник зоологии, 1993)
Some peculiarities, characteristic to Chiroptcrans only, are outlined for metatarsal bones prenatal development in common noctula, Nyctalus noctula. Certain evolutionary problems are discussed.